MISTAKE ANALYSIS OF CLASS X STUDENTS IN HANDAYANI SUNGGUMINASA HIGH SCHOOL IN COMPLETING THE PROBLEMS OF EQUATION AND EQUALITY EQUATION SQUARE - Nur Fadhilah Amir; M Yusran Zakaria (JME (Journal of Mathematics Education), 2019)
This type of research is descriptive qualitative research that presents the percentage of students' errors in solving mathematical problems, especially the questions of quadratic equations and squared inequalities. The research subjects were 22-grade students of SMA Serayani Sungguminasa, as many as 22 people. This study aims to determine the level of error made by class X SMA Handayani Sungguminasa students in solving quadratic equation problems and squared inequalities, especially conceptual errors, principle errors, and algorithmic errors. Data collection is done by providing an instrument in the form of a diagnostic test consisting of 6 items in the class essay with the intention to obtain the score of each type of error level. From the results of the analysis, the percentage of concept error rates was 39.77% (high), the principle error rate was 44.63% (high), and the algorithm error rate was 64.35% (very high). While in general, the level of error of class X students of Handayani Sungguminasa High School in completing the questions of quadratic equations and inequality squares is 54.85% or in the category, the level of error is very high.